A dual-functional social innovation process model for low-cost houses through university-enabled initiative. Issue 2 (8th April 2019) - Belayutham, Sheila; Che Ibrahim, Che Khairil Izam; Zulkifli, Assrul Reedza; Ibrahim, Norhati
Abstract : Purpose: The purpose of this study is to develop a dual-functional university-enabled social innovation process model on the subject of low-cost houses that addresses the distinct elements of social obligation and university teaching–learning. Design/methodology/approach: This study has predominantly adopted a longitudinal single case study approach, where data have been collected through interviews, survey, participant observation, direct observation and document review. The case study details on the social innovation processes, which was conducted by Universiti Teknologi MARA, Malaysia. Findings: This study has demonstrated the social innovation processes toward addressing the issue of insufficient low-cost houses, concurrently benefitting the teaching–learning dimension. Three sub-innovations have been highlighted in the developed social innovation process model, which are collaboration process, teaching–learning and design-construct innovation. Research limitations/implications: Because the study has been based on a single prototype project, further investigation is necessary to confirm the applicability of the full-fledged model. The established social innovation process model is also suggested to be tested in other social fields. Practical implications: The established social innovation process model has created a new perspective that enables universities to contribute in providing shelter for low-income families, simultaneously enhancing the teaching–learning dimension through experiential learning. Social implications: The dual-functional social innovation process model provides a synergistic relationship between the university and the society. Ultimately, the model could address social issues pertaining to low-income families with the built of low-cost houses, concurrently preparing graduates who are highly marketable, which could reduce the rate of graduate unemployment in the country. Originality/value: The development of the social innovation process model for low-cost houses through university-enabled initiative is a novel establishment, particularly for developing nations, as limited studies have been conducted in this regard. The significant insights into how university could play a role in addressing major social issues, along with their core focus (teaching–learning and research development), is a breakthrough for further diffusions of social innovation by universities.